The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/obr.13017
|View full text |Cite
|
Sign up to set email alerts
|

Targeting bile acid metabolism in obesity reduction: A systematic review and meta‐analysis

Abstract: A systematic review and meta-analysis was conducted of studies that address the association of bile acid (BA) with obesity and of studies on the effects of treatment in patients with obesity on BA metabolism, assessed from systemic BA, fibroblast growth factor 19 (FGF19), 7α-hydroxy-4-cholesten-3-one (C4) level, and faecal BA. We searched PubMed, Embase, and the Cochrane Library from inception to 1 August 2019 using the keywords obesity, obese, body mass index, and overweight with bile acid, FGF19, FXR, and TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 105 publications
(97 reference statements)
1
14
0
Order By: Relevance
“…It is a well observed fact that bariatric procedures significantly reduce levels of cholesterol and LDL cholesterol ( 24 ). Among the hypothesized mechanisms contributing to reduced cholesterol levels after bariatric surgery are a decreased intestinal cholesterol absorption, an increased trans-intestinal cholesterol excretion as well as an increased flux of cholesterol into bile acid synthesis due to augmented fecal excretion of bile acids ( 25 , 26 ). Interestingly, there are studies suggesting a direct role of DPP4 in the regulation of cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is a well observed fact that bariatric procedures significantly reduce levels of cholesterol and LDL cholesterol ( 24 ). Among the hypothesized mechanisms contributing to reduced cholesterol levels after bariatric surgery are a decreased intestinal cholesterol absorption, an increased trans-intestinal cholesterol excretion as well as an increased flux of cholesterol into bile acid synthesis due to augmented fecal excretion of bile acids ( 25 , 26 ). Interestingly, there are studies suggesting a direct role of DPP4 in the regulation of cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown a link between increasing BMI and primary BAD although – unlike ours – have not performed direct comparisons of BAD prevalence rates in patients with chronic diarrhoea stratified according to the World Health Organisation weight classification system [ 20 , 21 , 33 ]. The link between increasing BMI and primary BAD is intriguing, with a recent systematic review and meta-analysis confirming altered bile acid metabolism in obesity [ 34 ]. This is evidenced by individuals with obesity having lower serum FGF19, elevated serum bile acid precursors, increased bile acid synthesis and luminal excretion, with shorter colonic transit times [ 3 , 21 , [33] , [34] , [35] ].…”
Section: Discussionmentioning
confidence: 99%
“…The link between increasing BMI and primary BAD is intriguing, with a recent systematic review and meta-analysis confirming altered bile acid metabolism in obesity [ 34 ]. This is evidenced by individuals with obesity having lower serum FGF19, elevated serum bile acid precursors, increased bile acid synthesis and luminal excretion, with shorter colonic transit times [ 3 , 21 , [33] , [34] , [35] ]. The pathophysiological basis for this association is unclear, although some plausible explanations have been provided.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that bariatric surgery leads to an increase in plasma levels of bile acids (BA) [51][52][53][54][55][56]. After RYGB, an increase was found in fasting and postprandial BA, with parallel alterations in composition.…”
Section: Bile Acidsmentioning
confidence: 99%